A Long and Winding Path Through Space Weather Research - Bruce T. Tsurutani (Perspectives of Earth and Space Scientists)
Abstract I have written my scientific bio concerning various topics of Space Weather with the aim of coming up with pointers to help young people with their careers. I have worked in other areas of Space Physics, but to include them would make this article even more disjoint than this article is already. I will introduce encounters with some of our scientific “luminaries” that were instrumental in my career. One of them, my thesis advisor at University of California at Berkeley, Kinsey Anderson said “whatever you do while doing science, have fun”. This is about the best piece of advice that I can pass down to you no matter what path you take, doing detailed data analysis research, theory or management. Moral #1. Listen to your elders. They can give you great advice! Sometimes. I will offer other pieces of advice, but will sometimes not call them out specifically.